2021
DOI: 10.1144/jgs2020-177
|View full text |Cite
|
Sign up to set email alerts
|

Emplacement of the Little Minch Sill Complex, Sea of Hebrides Basin, NW Scotland

Abstract: The Little Minch Sill Complex is comprised of a series of stacked, multi-leaved Paleocene aged dolerite sills, which have been primarily intruded into Mesozoic sedimentary rocks and Paleocene tuffs/?hyaloclastites within the Sea of Hebrides Basin, situated on the NE Atlantic margin. Two previously proposed models for the emplacement of the sill complex have opposing ideas for the location of magma input and emplacement mechanisms. Both models have been constructed using data primarily from onshore outcrops, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…So far, we have described the smallest building blocks of sheet intrusions (i.e., magma fingers and segments) and placed them within our new element-based terminology. In addition, numerous studies have shown that sheet intrusions can occasionally be subdivided into larger sections, each of which is created by the amalgamation of an element set (e.g., Thomson and Hutton, 2004;Hansen and Cartwright, 2006a;Miles and Cartwright, 2010;Schofield et al, 2012b;Magee et al, 2016a;Schofield et al, 2017;Fyfe et al, 2021). For example, where elements define a group of fanning magma fingers and/or segments, these larger sections have been termed lobes (e.g., Thomson and Hutton, 2004;Hansen and Cartwright, 2006a;Schofield et al, 2012b).…”
Section: Elements and Their Connectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, we have described the smallest building blocks of sheet intrusions (i.e., magma fingers and segments) and placed them within our new element-based terminology. In addition, numerous studies have shown that sheet intrusions can occasionally be subdivided into larger sections, each of which is created by the amalgamation of an element set (e.g., Thomson and Hutton, 2004;Hansen and Cartwright, 2006a;Miles and Cartwright, 2010;Schofield et al, 2012b;Magee et al, 2016a;Schofield et al, 2017;Fyfe et al, 2021). For example, where elements define a group of fanning magma fingers and/or segments, these larger sections have been termed lobes (e.g., Thomson and Hutton, 2004;Hansen and Cartwright, 2006a;Schofield et al, 2012b).…”
Section: Elements and Their Connectorsmentioning
confidence: 99%
“…13B). This highlights that elongate sills may not always be fed via an underlying dyke striking parallel to the intrusion's long axis (e.g., Galerne et al, 2011;Fyfe et al, 2021) and that pre-existing fault planes can greatly influence sill geometries.…”
Section: Sill S2mentioning
confidence: 99%
“…2). It is clear from seismic reflection data that Paleocene sills are extensively distributed across the basin (Chesher et al 1983;Emeleus & Bell 2005;Schofield et al 2016;Fyfe et al 2021). In the MB Paleocene volcanic rocks are largely absent, with most igneous intrusions believed to have terminated at the Rubha Reidh Ridge (Fyfe et al 1993;Fyfe et al 2021).…”
Section: Geological Historymentioning
confidence: 99%
“…It is clear from seismic reflection data that Paleocene sills are extensively distributed across the basin (Chesher et al 1983;Emeleus & Bell 2005;Schofield et al 2016;Fyfe et al 2021). In the MB Paleocene volcanic rocks are largely absent, with most igneous intrusions believed to have terminated at the Rubha Reidh Ridge (Fyfe et al 1993;Fyfe et al 2021). An exception is the Minch magnetic anomaly, which is interpreted to be a single major dyke, which strikes NW-SE for 110 km across the basin (Ofoegbu & Bott 1985;Fyfe et al 1993).…”
Section: Geological Historymentioning
confidence: 99%
See 1 more Smart Citation